A Review of Control and Power Allocation Methods on Cellular Communication Systems - Diky Siswanto,Fachrudin,Mohammad Mukhsim (International Conference on Industrial Revolution for Polytechnic Education, 2021)
In mobile communication, the received signal quality is influenced by the received interference, as well as by the propagation channel conditions. In order to maximize system performance, the radio resource allocation cannot be applied merely by increasing the transmission signal power. In which, it will be the interference source for neighboring cells. Some power allocation methods for cellular systems have been offered. Meanwhile, the cellular communication system has undergone evolution following the needs of the frequency bandwidth of their users. The difference signal processing techniques of each system have an impact on the performance and characteristics of the system. To find the best strategies of power control for cellular communication systems needs to understand the system characteristics; so that optimal results can be achieved.